Valuating wetland ecosystem services based on the discrete choice experiments: a systematic review and meta-analysis - Kong, Senquan; W. Mohamad, Wan Norhidayah; Rosland, Anitha; Lee, Yuanyuan (Horizon Research Publishing, 2025)
This study conducts a systematic review and meta-analysis of wetland ecosystem service values based on discrete choice experiments across 49 studies from 22 countries. It finds that the expansion of wetland areas negatively impacts public willingness to pay (WTP) for conservation, with a 1% increase in wetland areas leading to a 0.66% decrease in WTP, particularly in developed countries. However, larger wetland areas positively affect the total value of ecosystem services, with a 1% increase in the area contributing to a 0.337% rise in service value. The study also reveals that higher GDP, cultural values, and biodiversity significantly enhance WTP, with wealthier nations and wetlands offering cultural or biodiversity benefits seeing higher public support for conservation. The research suggests that policies should prioritize improving the quality and functionality of existing wetlands rather than solely expanding their area. Additionally, integrating cultural and biodiversity values into conservation plans can increase public participation and willingness to pay. For developed countries, improving existing wetland services is key, while developing countries should focus on both expanding and enhancing wetland quality. These findings emphasize the need for balanced, quality-focused wetland conservation strategies that maximize ecological and socio-economic benefits.